2020
DOI: 10.1111/gcb.15308
|View full text |Cite
|
Sign up to set email alerts
|

Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties

Abstract: Global impacts of fertilization and herbivore removal on soil net nitrogen Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties mineralization are modulated by local climate and soil properties

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 76 publications
1
27
0
Order By: Relevance
“…In contrast, a recent meta-analysis (Zhou et al, 2017) and a continental-scale experiment (Risch et al, 2020) indicated that soil C and N mineralization were increased or were unaffected by grazing, suggesting that the effect of grazing on C and N mineralization depends on spatial scale and grassland type. The strong associations of plant substrates (plant C:N ratio and BGB) with C or N mineralization rates in the surface soil layer in the current study are reasonable because these substrates are the main sources of energy for soil microorganisms (Dungait et al, 2012).…”
Section: Effect Of Grazing On Soil Functions In Surface and Deep Soil...mentioning
confidence: 86%
“…In contrast, a recent meta-analysis (Zhou et al, 2017) and a continental-scale experiment (Risch et al, 2020) indicated that soil C and N mineralization were increased or were unaffected by grazing, suggesting that the effect of grazing on C and N mineralization depends on spatial scale and grassland type. The strong associations of plant substrates (plant C:N ratio and BGB) with C or N mineralization rates in the surface soil layer in the current study are reasonable because these substrates are the main sources of energy for soil microorganisms (Dungait et al, 2012).…”
Section: Effect Of Grazing On Soil Functions In Surface and Deep Soil...mentioning
confidence: 86%
“…Soil microbial biomass and N. Grassland microbial biomass and microbial biomass C:N chemistry was unchanged in response to NutNet's consistently increased N supply across a wide range of climatic and edaphic conditions [77][78][79]. Although N did not generally reduce soil pH, N supply reduced microbial genes associated with metabolism, reducing both microbial growth and respiration, particularly in surface soils [78,80].…”
Section: Consumers -Soil Microbial Communitiesmentioning
confidence: 99%
“…+ and NO 3 − concentration and pH (Risch et al, 2020). Another subsample was sieved (4 mm) and used to determine the N-cycling functional microbial communities (six samples per site).…”
Section: Study Sites and Experimental Designmentioning
confidence: 99%